Assessment Re-Think: Income-Generating and Industry-Based Assessments - de Souza-Daw, Tony; Di Serio, Antony; Falah, Ahmed; Fahd, Kiran; Parvin, Sazia (International Journal of Asian Education, 2022)
Assessments are the fundamental media between students and educators. This paper aims to evaluate how to create assessments, how students learn from them, and how to link them to the industry and entrepreneurism. The implementation plan postulates how students can generate income from income-generation assessments or business innovation assessments. In this paper, we discuss the involvement of modern industry in assessment. We examine evidence from approximately 100 assessments detailed in 32 subject outlines. We employ a descriptive, pragmatic research methodology to consider whether they can be aligned more with industry expectations and expected duties. We propose a framework to connect with industry and create student income-generating projects. This proposed income-generating assessments framework recommended industry-based assessments with which students can not only earn marks towards a subject but potentially earn an income based on it. This paper extends the idea of peer learning to expert or industry learning: an approach that did not employ in higher education. Our approach supports educators in keeping the assessment up-to-date, enabling students to add more value to their learning of industry products and procedures. Students can directly contribute to the product and procedures and learn from the strategies actively employed in the workplace.